Clinical Evaluation of Shatyadi Churna and Virechana Karma in the Management of Tamaka Shwasa w.s.r to Bronchial Asthma - Raina, Namartha; sharma, Rajesh (International Research Journal of Ayurveda & Yoga, 2022)
Background-Tamaka Shawasa is said to be “Yapya vyadhi” i.e not only curable but managed by medicine, but can be cured if it is of acute origin as said by Ayurvedya Charak. Materials and methods- It was done on 30 Patients of Tamaka Shwasha. They were treated on the principle of Ayurveda & evaluation of Virechanakarma & Shatyadi churna. Results-Overall effect is that in 33.33% i.e 1 out of 30 patients cases complete remission is seen, 26.66% cases shown marked improvement, 53.33% cases shown moderate improvement, 16.66% cases reported mild improvement & 0.00% cases were having no change in their symptoms. Conclusion- Ayurveda treatment not only cure the root cause of disease but prevent the disease in future recurrence by boosting the immunity against the infection and treating allergic reactions. This article proves clinical evaluation of Shatyal Churana And Virechana Karma in management of Tamaka Shwasa w.s.r “ Bronchial Asthma”.